2003
DOI: 10.1074/jbc.m305991200
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived Growth Factor-BB-mediated Activation of Akt Suppresses Smooth Muscle-specific Gene Expression through Inhibition of Mitogen-activated Protein Kinase and Redistribution of Serum Response Factor

Abstract: Platelet-derived growth factor (PDGF) inhibits expression of smooth muscle (SM) genes in vascular smooth muscle cells and blocks induction by arginine vasopressin (AVP). We have previously demonstrated that suppression of SM-␣-actin by PDGF-BB is mediated in part through a Ras-dependent pathway. This study examined the role of phosphatidylinositol 3-kinase (PI3K)y and its downstream effector, Akt, in regulating SM gene expression. PDGF caused a rapid sustained activation of Akt, whereas AVP caused only a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 54 publications
(58 reference statements)
5
46
1
Order By: Relevance
“…The growth medium does not contain insulin; relevant molecules include calcium (1.8 mM), phosphate (1.014 mM), and glucose (5.6 mM). VSMC primary cultures were used up to the ninth passage (14). All cells were placed in serum-reduced medium (≤0.2% serum) for 24 hr to maintain quiescence prior to further treatment.…”
Section: Cell Culturementioning
confidence: 99%
“…The growth medium does not contain insulin; relevant molecules include calcium (1.8 mM), phosphate (1.014 mM), and glucose (5.6 mM). VSMC primary cultures were used up to the ninth passage (14). All cells were placed in serum-reduced medium (≤0.2% serum) for 24 hr to maintain quiescence prior to further treatment.…”
Section: Cell Culturementioning
confidence: 99%
“…Cells (passages 4 -12) were grown in Eagle's minimal essential medium containing 1 mM L-glutamine, 2 g/liter NaHCO 3 , 100 international units/ml penicillin, 100 g/ml streptomycin, and 10% (v/v) fetal calf serum at 37°C in a humidified air/CO 2 (19:1) atmosphere. For the stable transfections of VSMC with H-Ras, Myr-Akt, and G␣ 16 , cDNAs encoding either Akt containing the Src myristoylation sequence (15), the GTPase-deficient, constitutively active forms of the human T24 H-Ras with V12 (G12V) mutation (14), or GTPase-deficient G␣ 16 (␣ 16 Q212L) (12) were packaged into a replication-defective retrovirus by the procedure described previously (26). Secreted retrovirus was supplemented with Polybrene (8 g/ml), filtered (0.45 m), and incubated with VSMC for 48 h. Cells expressing myristoylated Akt, H-Ras, or G␣ 16 were selected by culturing them in medium containing G418 (500 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…VSMC were stimulated with PDGF-BB for 6 or 24 h, and gene expression was compared with control cells Tables A and B). Our laboratory previously showed that PDGF-BB-mediated suppression of SM-specific gene expression is partly mediated by activation of both the H-Ras and phosphatidylinositol 3-kinase/Akt pathways (14,15). To investigate the contribution of these pathways to the changes in the global gene expression profile induced by PDGF, we compared the increases and decreases induced by PDGF stimulation to the changes seen in VSMC stably expressing H-Ras (14) or constitutively active Myr-Akt (15) (see Supplementary Tables A and B).…”
Section: Changes In Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations